An integrated MEMS piezoresistive tri-axis accelerometer - 张永平 何常德 于佳琪 杜春晖 张娟婷 丑修建 张文栋 (Journal of semiconductors, 2013)
An integrated MEMS accelerometer has been designed and fabricated. The device, which is based on the piezoresistive effect, accomplishes the detection of three components of acceleration by using piezoresistors to compose three Wheatstone bridges that are sensitive to the only given orientation. The fabrication of the accelerometer is described, and the theory behind its operation developed. Experimental results on sensitivity, crossaxis-coupling degree, and linearity are presented. The sensitivity of X, Y and Z were 5.49 mV/g, 5.12 mV/g and 4.82 mV/g, respectively; the nonlinearity of X, Y and Z were 0.01%, 0.04% and 0.01%, respectively; the crossaxis-coupling factor of X axis to Y axis and Z axis are 0.119% and 2.26%; the cross-axis-coupling factor of Y axis to X axis and Z axis are 0.157% and 4.12%; the cross-axis-coupling factor of Z axis to X axis and Y axis are 0.511% and 0.938%. The measured performance indexes attain accurate vector-detection in practical applications, and even at a navigation level. In conclusion, the accelerometer is a highly integrated sensor.